Implementasi Standar Nasional Pendidikan dalam Meningkatkan Daya Saing SD IT Abu Bakar Ash- Shiddiq Rajapolah - Ari Syamsul Bahri (Program Studi Manajemen Pendidikan Islam, 2023)
This article aims to analyze the implementation of national education standards in increasing the competitiveness of Sekolah Dasars, considering that these standards are an important issue for the management of education. The research method used in this research is descriptive (exposure). Primary data were obtained from direct observation and interviews. Secondary data is data obtained from written sources related to this research. The results showed that the implementation of national education standards in improving the competitiveness of SD IT Abu Bakar Ash- Shiddiq Rajapolah has not been well realized by referring to the eight national education standards so that it can increase the competitiveness of Sekolah Dasars meskipun obtain an A accreditation score.